Les limites de l’acceptable : petites et grandes « perversions » - Julie Mazaleigue-Labaste (Criminocorpus, 2016)
This essay retraces the history of a divide that is central for the conceptualisation, theorisation and experience of sexuality in individualistic and liberal democratic contemporary societies: the divide between “minor” and “major” perversions, which draws the boundaries of acceptable sexuality. I will thus retrace the history of “sexual perversion” as a psychopathological category from the xixth century French alienism to the DSM-5 (2013), and I will analyse its relations with cardinal values expressed in norms that regulates human interactions in the liberal democratic societies. I assume the gradual disqualification of non self-controlled sexual desires and behaviours and of sexual violence has been the main condition of a liberalisation and democratisation of minor sexual deviances process.